Leadership in Regional Tourism Design Education: Integrating Drone Visualisation with Design Thinking, Peer-to-Peer Collaboration, Shared Problem Solving and Stakeholder Engagement - Hiroko Oe; Hirotaka Nakagawa (Business Ethics and Leadership)
This study presents an innovative leadership development framework for regional tourism design education, where drone technology catalyses transformative leadership skills through collaborative learning and enhanced visualisation. Pilot research across three Japanese heritage tourism sites (Hakone, Choshi, and Nikko) engaged 20 emerging leaders in interactive group processes, demonstrating how shared aerial perspectives foster strategic thinking and a comprehensive understanding of the unique challenges in regional tourism development. Integrating service design thinking and systems theory with aerial visualisation cultivated three dimensions of leadership development: strategic vision (through peer-to-peer collaboration), technical competency (through shared problem-solving), and stakeholder engagement capabilities. Structured leadership exercises using the KJ method and GIS mapping enabled participants to develop strategic approaches to regional tourism challenges while rotating through key leadership positions, thus enhancing individual and collective growth. Findings showed that this approach inspired 90% of participants to pursue drone operation certification and 85% to implement innovative tools for community leadership. Drone-based visualisation of regional assets created a platform for developing strategic insight, with 92% of emerging leaders reporting enhanced spatial awareness and decision-making. The framework’s success highlights the potential of integrating drone technology and collaborative methods to effectively cultivate next-generation leaders in regional tourism development.